Frequency of Aberrant Right Subclavian Artery in Single Centre Patients undergoing Coronary Angiogram via Radial Artery Approach - Khan, Farhat Ullah; Ullah, Ejaz; Khan, Muhammad Idrees; Rashid, Farhana; Musa, Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of ARSA in patients undergoing CAG via the radial artery approach at Hayatabad Medical Complex, Peshawar. The study also aimed to assess the impact of ARSA on the procedural success rate. Methodology: This retrospective study included 500 patients who underwent CAG between January 2023 and December 2023. Data were collected from medical records, angiographic reports, and pre-procedural imaging, including CTA. Statistical analysis was performed using the Chi-square test to assess the relationship between ARSA and procedural success. Results: The study found that 60% of the patients were diagnosed with ARSA, and 40% were not. The success rate of CAG via the radial artery approach was 80%, with 20% requiring femoral artery access. A statistically significant relationship was found between ARSA and the success of radial artery access (p-value = 0.04). The most common comorbidities were hypertension (37%), diabetes (25%), and cholesterol (18%). The p-value for the association between comorbidities and ARSA was 0.12. Conclusion: ARSA is prevalent in a significant proportion of patients undergoing CAG via the radial artery approach. Pre-procedural imaging, such as CTA, is crucial for detecting ARSA and improving procedural success. The study highlights the importance of considering alternative access routes in patients with ARSA to minimize complications.